Leadless pacemaker implant in patients with pre‐existing infections: Results from the Micra postapproval registry. (28th January 2019) - El‐Chami, Mikhael F.; Johansen, Jens Brock; Zaidi, Amir; Faerestrand, Svein; Reynolds, Dwight; Garcia‐Seara, Javier; Mansourati, Jacques; Pasquie, Jean‐Luc; McElderry, Hugh Thomas; Roberts, Paul R.; Soejima, Kyoko; Stromberg, Kurt; et al.
Abstract: Introduction: Leadless pacemakers may provide a safe and attractive pacing option to patients with cardiac implantable electronic device (CIED) infection. We describe the characteristics and outcomes of patients with a recent CIED infection undergoing Micra implant attempt. Methods and Results: Patients with prior CIED infection and device explant with Micra implant within 30 days, were identified from the Micra post approval registry. Procedure characteristics and outcomes were summarized. A total of 105 patients with prior CIED infection underwent Micra implant attempt ≤30 days from prior system explant (84 [80%] pacemakers and 13 [12%] ICD/CRT‐D). All system components were explanted in 93% of patients and explant occurred a median of 6 days before Micra implant, with 37% occurring on the day of Micra implant. Micra was successfully implanted in 99% patients, mean follow‐up duration was 8.5 ± 7.1 months (range 0‐28.5). The majority of patients (91%) received IV antibiotics preimplant, while 42% of patients received IV antibiotics postprocedure. The median length of hospitalization following Micra implant was 2 days (IQR, 1‐7). During follow‐up, two patients died from sepsis and four patients required system upgrade, of which two patients received Micra to provide temporary pacing support. There were no Micra devices explanted due to infection. Conclusion: Implantation of the Micra transcatheter pacemaker is safe and feasible in patients with a recent CIED infection. No recurrent infections that required Micra device removal were seen. Leadless pacemakers appear to be a safe pacing alternative for patients with CIED infection who undergo extraction.